MANAGEMENT MODEL OF ILLEGAL LOGGING CONFISCATED GOODS AT RUPBASAN INSTITUTIONS IN THE PROVINCE - Subaidi, Joelman; Syahputra, Dedy; Jafar, Sofyan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Management of confiscated illegal logging goods in general has been regulated by the Decree of the Director General of Corrections Number E2.UM.01.06 of 1986, and has been completed by Decree of the Director General of Corrections Number E1.35.PK.03.10 of 2002 concerning Implementation Guidelines and Technical Instructions for the Management of Confiscated Objects The State and the State's Loot in Rupbasan. The same thing is also regulated in Article 44 of the Criminal Code which states "confiscated goods are deposited at the General Meeting of Shareholders". However, the implementation of the confiscation of illegal logging itself, both found and confiscated timber is regulated in the Ministry of Forestry Regulation Number: P.48/Menhut-II/2006 concerning Guidelines for the Implementation of Auction of Finding, Confiscated and Looted Forest Products. The specific objectives of this study are to identify and analyze the management arrangements for confiscated illegal logging goods at the Rupbasan in Aceh Province and the management of confiscated illegal logging goods at the Rupbasan in Aceh Province. acceptance, research, registration, storage, maintenance, transfer, rescue, security, release and deletion as well as reporting. This is in accordance with the Decree of the Director General of Corrections Number E1.35.PK.03.10 of 2002 concerning Implementation Guidelines and Technical Guidelines for the Management of State Confiscated Goods and State Loot at Rupbasan which is a refinement of the Decree of the Director General of Corrections Number E2.UM.01.06 of 1986 . The unavailability of facilities and infrastructure in the form of warehouses at Rupbasan in Aceh is a problem experienced by Rupbasan in the management of confiscated goods from illegal logging, and the wide working area of Rupbasan agencies in Aceh is a separate problem in the management of confiscated goods from illegal logging. The Government is advised to provide adequate warehouses for storing confiscated goods at the Rubsahan in Aceh, and to establish a minimum of 5 (five) Rupbasan agencies with working areas of 4 to 5 districts/cities.